Impact of Diabetes Mellitus upon the Physical Activity of Patients Post Coronary Artery Bypass Graft Surgery in Baghdad City - Khalida Alwan Mansour; Musaab Majid Abdul wahhab (Kufa Journal for Nursing Sciences)
Background: Diabetes mellitus is considered a major risk factor for developing coronary artery disease, and is associated with a marked increase in the complications post cardiac revascularization in both women and men in addition to its impact on the patients Quality of life.